The impact of the war on the economic development of Ukraine - Nataliia Slaviuk; Tetiana Bui (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
As of summer 2022, the war in Ukraine has lasted more than three months, caused the deaths of thousands of people, and ruined the lives of millions. It has impacted the world economy and affected Ukraine severely, ruining industries as well as causing massive migration, a decrease in household income, and an increase in the budget deficit and government debt. As the war continues, it will deepen the negative effects on the economy. We think that one of the reasons for Russia's aggression is Ukraine's desire to integrate into the Western world and its economic development over the last years. We believe that joint efforts of the Ukrainian government, European institutions, and civil society will help end the war and rebuild the country.
Keywords: 330; Kriegsfolgen; Ukraine